Ensuring Sustainable Employment Rights in Vietnamese Labor Law in the Face of Digital Transformation - Thi, Tamhoa Nguyen; Duc, Hiep Ho (Jurnal Cita Hukum, 2026)
The purpose of this study is to clarify how Vietnamese labor law ensures sustainable employment rights for workers in the context of digital transformation, which is profoundly changing the structure of the labor market, forms of employment, and labor relations. The study focuses on analyzing the adaptability of current labor law regulations to the increase in digitalized and flexible labor, while assessing legal gaps that may increase the risk of job loss or a decline in job quality. The study uses a textual research method, combining a quantitative survey of 229 workers and employers in sectors directly affected by digital transformation with semi-structured interviews with 21 state management experts, lawyers, policy researchers, and business representatives to clarify perceptions, practical experiences, and policy evaluations. The research results show that Vietnamese labor law has made certain progress in protecting employment rights through regulations on labor contracts, retraining, and social security. However, it still has limitations in covering new forms of employment as well as mechanisms to ensure safe job transitions for workers. Based on this, the study affirms the scientific and practical significance of improving labor law towards a sustainable employment-centered approach, contributing to enhancing the adaptability of the labor market and ensuring social stability in the digital transformation era.